UJI ADAPTASI BEBERAPA VARIETAS SORGUM MANIS DI LAHAN KERING WILAYAH JAWA TENGAH DAN JAWA TIMUR - Muji Rahayu; Samanhudi Samanhudi; Wartoyo Wartoyo (Universitas Sebelas Maret, 2012)
The research was conducted from May to November 2011 at Central Java (Karanganyar District) and East Java (ngawi district) dry land. The research was used Randomized Complete Block Design (RCBD) and with two treatments, were: sweet sorghum varieties (Numbu dan Kawali) and the kind of manure (chicken, goat, cow, kascing and without manure). The data was analyzed with randomize analisys and Duncan test. The research showed that (a) Numbu and Kawali varieties were gave same respons to growth and yield component variables, so the both varieties can be planting at Central Java (Karanganyar District) and East Java (Ngawi District) dry land; (b) Chicken manure gave the best effect to sweet sorghum growth and yield compared with control, cow, goat, and kascing manure, consist of: plant height, leaf number, root length, root volume, 1000 seed weight, stem diameter, biomass fresh weight, and biomass dry weight, juice content, and sugar content.